Efektivitas Cognitive Behavior Therapy (CBT) untuk Mereduksi Self-Criticism pada Siswa Kelas IX di MTs Negeri 2 Jember - Soraya, Ines; Rahmawati, Weni Kurnia; Fauziyah, Nailul (SENTRI: Jurnal Riset Ilmiah, 2025)
Excessive self-criticism is a common psychological problem experienced by students and has a significant impact on mental health and academic achievement. Self-criticism is the tendency to set high standards for oneself and then punish oneself if they do not meet those standards. This research seeks to evaluate the efficacy of Cognitive Behavior Therapy (CBT) in reducing self-criticism in students of MTs Negeri 2 Jember. The approach applied was a quasi-experimental design involving pretest-posttest with control groups, comprising 30 students recruited through purposive sampling, with 8 participants as the sample who had high levels of self-criticism. The instrument used was a self-criticism scale with three indicators: Inadequate Self, Hated Self, and Reassured Self. The results showed that the application of Cognitive Behavioral Therapy was significantly effective in reducing self-criticism in MTs students. The independent samples t-test revealed a notable variance between control groups, yielding a p-value of 0.000 (<0.05). CBT has been shown to significantly reduce self-criticism scores from high to moderate or low. Therefore, CBT can be an effective approach to supporting students' mental health, particularly in addressing tendencies to blame and devalue themselves excessively.